Reverse Proof System In Gratification In Criminal Acts Of Corruption - Muhammad Rifaldy Palorongi Hamid; Nurul Qamar; Hardianto Djanggih (COMPENDIUM OF JUDGE MADE LAW, 2025)
This study aims to examine the application of the reversal of the burden of proof in gratification-related corruption cases, using Decision No. 45/Pid.Sus-TPK/2021/PN Mks as a case study. In the context of Indonesian law, the reversal of the burden of proof is a legal mechanism that enables defendants to demonstrate that the gratuities received are not connected to acts of corruption. This research adopts a normative juridical method combined with a case study approach to analyze how judges interpret and implement the reversal of proof provisions as stipulated in Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 on the Eradication of Corruption. The findings indicate that the panel of judges concluded the defendant failed to prove that the received gratuities were unrelated to their official position or authority. Consequently, the reversed burden of proof did not exonerate the defendant from legal accountability. These results highlight the inherent challenges defendants face in fulfilling the evidentiary burden and underscore the necessity for a comprehensive understanding of both substantive and procedural aspects of law in the application of reversed proof mechanisms. This research is expected to contribute to the development of criminal procedural law, particularly in corruption cases in Indonesia.